2007
DOI: 10.1101/gr.5720807
|View full text |Cite
|
Sign up to set email alerts
|

A novel view of the transcriptome revealed from gene trapping in mouse embryonic stem cells

Abstract: Embryonic stem (ES) cells are pluripotent cell lines with the capacity of self-renewal and the ability to differentiate into specific cell types. We performed the first genome-wide analysis of the mouse ES cell transcriptome using ∼250,000 gene trap sequence tags deposited in public databases. We unveiled >8000 novel transcripts, mostly non-coding, and >1000 novel alternative and often tissue-specific exons of known genes. Experimental verification of the expression of these genes and exons by RT-PCR yielded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Polyadenylated noncoding RNA transcripts have become increasingly interesting as their prevalence has become more appreciated (Goodrich and Kugel 2006;Mattick and Makunin 2006;Pang et al 2006;Kapranov et al 2007a,b;Pauler et al 2007;Prasanth and Spector 2007;Roma et al 2007). These transcripts include precursors of small regulatory RNAs but also are related to a number of other processes.…”
Section: Discussionmentioning
confidence: 99%
“…Polyadenylated noncoding RNA transcripts have become increasingly interesting as their prevalence has become more appreciated (Goodrich and Kugel 2006;Mattick and Makunin 2006;Pang et al 2006;Kapranov et al 2007a,b;Pauler et al 2007;Prasanth and Spector 2007;Roma et al 2007). These transcripts include precursors of small regulatory RNAs but also are related to a number of other processes.…”
Section: Discussionmentioning
confidence: 99%
“…By estimation, only 50-70% of all mouse genes have been trapped in the past. Some genes have been trapped more than once while some vectors inserted into noncoding regions (Abuin et al, 2007;Roma et al, 2007Roma et al, , 2008Schnutgen et al, 2008). Many experiments have shown the bias of trapping vectors and some ''cold'' genomic spots on the chromosomes have remained untrapped (Austin et al, 2004;Schnutgen et al, 2008;Shigeoka et al, 2005).…”
Section: Igtc-the International Gene Trap Consortiummentioning
confidence: 98%
“…By knocking out genes, the different functions of these genes have been annotated, including functions in development, metabolism (Kondo et al, 2006;Moreadith and Radford, 1997;Yen et al, 2006), the neural system (Buss et al, 2006;Russell, 2007;Walz et al, 2002;Wang et al, 2007), apoptosis (Altman et al, 2008;Wang et al, 2006) and cancer (Boominathan, 2007;Gerits et al, 2007;Kondo et al, 2006;Wu et al, 2008). As a high-throughput gene knockout strategy, gene trapping has other unique applications, such as finding new coding sequences, and reporting the expression level of a gene flanking the insertion site (Matsuda et al, 2004;Roma et al, 2007). Knocking out mouse genes has also opened up other areas of science especially in medical research.…”
Section: Perspectivesmentioning
confidence: 99%
“…A large number of ESTs and SAGE tags with no match to a known gene were found to be abundantly and specifically expressed in ES cells Richards et al, 2004). In addition, the analysis of gene trap screens revealed thousands of novel exons and genes, many of which are found in gene trapping hotspots associated with loci significantly expressed in ES cells (Roma et al, 2007). Further studies identified naturally occurring antisense transcripts for several pluripotency genes, including Oct4 and Nanog, suggesting that sense-antisense pairing may have a role in regulation of pluripotency (Richards et al, 2006).…”
Section: Stembookorgmentioning
confidence: 99%